2012
DOI: 10.4236/msa.2012.39085
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue Crack Growth on Double Butt Weld with Toe Crack of Pipelines Steel

Abstract: The welded structures have a broad applicability (car industry, aeronautical, marine, pipelines, etc.). The welding being an assembled process, presents both advantages and disadvantages. A simple existing defect after welding can generate a catastrophic fracture. This work studies the fatigue crack growth of double butt weld with toe crack. Two types of pipeline material are studied with knowing API 5L grades X60 and X70 where tension form of loading is applied. In order to predict the fatigue behavior of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…13 represents the evolution of the specific energy expended U per cycle in function of ΔK in the three zones studied. This energy is given by the following relation [31], [55]:…”
Section: Evolution Of Energy Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…13 represents the evolution of the specific energy expended U per cycle in function of ΔK in the three zones studied. This energy is given by the following relation [31], [55]:…”
Section: Evolution Of Energy Parametersmentioning
confidence: 99%
“…The finite element analysis performed by Hadjoui [30] for the X60 and X70 steels for a load ratio R = 0.2 shows that the X70 presents a better resistance to fatigue. Recently Maachou [31] analyzed the fatigue crack growth behavior under constant amplitude and variable amplitude loading using terms of energy parameters. The main objective of this work is to study the fatigue crack growth rate of low-carbon micro alloyed steel X70 welded joints used in pipeline manufacturing.…”
Section: Introductionmentioning
confidence: 99%
“…In exploitation, welded constructions, as well as joints, are often affected by cyclic loading. Such loadings facilitate a crack initiation [1] and its propagation [2], often in the welded section [3]. The initiation of cracks in a welded joint occurs in places of the greatest stress concentration, i.e., in the toe radius.…”
Section: Introductionmentioning
confidence: 99%
“…Systematic studies have shown that, for instance, welding residual stresses might lead to a drastic reduction in the fatigue strength of welded elements. In multi-cycle fatigue (N > 106 cycles), the effect of residual stresses is comparable to the effect of stress concentration [4]. Surprisingly, the effect of residual stresses on the fatigue life of welded elements, specifically with regards to relieving harmful tensile residual stresses and introducing beneficial compressive residual stresses in the weld toe zones, is significant.…”
Section: Introductionmentioning
confidence: 99%